2019
DOI: 10.1177/1362361319886246
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety in young people with autism spectrum disorder: Common and autism-related anxiety experiences and their associations with individual characteristics

Abstract: Anxiety is common in autism spectrum disorder. Many anxiety symptoms in autism spectrum disorder are consistent with Diagnostic and Statistical Manual of Mental Disorders (5th ed.) anxiety disorders (termed “common” anxieties), but others may be qualitatively different, likely relating to autism spectrum disorder traits (herein termed “autism-related” anxieties). To date, few studies have examined both “common” and “autism-related” anxiety experiences in autism spectrum disorder. We explored caregiver-reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 69 publications
(155 reference statements)
1
28
0
1
Order By: Relevance
“…These results are congruent with the wider ASD literature (e.g. Bearss et al, 2016;Lau et al, 2020;Ozsivadjian et al, 2012;Robertson et al, 2018). Conversely, review findings are incongruent with this literature base in that anxiety was not commonly shown to be triggered by social situations.…”
Section: Summary and Critique Of Evidence: Assessment Studiessupporting
confidence: 79%
See 1 more Smart Citation
“…These results are congruent with the wider ASD literature (e.g. Bearss et al, 2016;Lau et al, 2020;Ozsivadjian et al, 2012;Robertson et al, 2018). Conversely, review findings are incongruent with this literature base in that anxiety was not commonly shown to be triggered by social situations.…”
Section: Summary and Critique Of Evidence: Assessment Studiessupporting
confidence: 79%
“…While there were only five assessment studies, collectively they indicate the nature of anxiety to be distinct in ASD, as demonstrated by non-technology-based research (e.g. Lau et al, 2020;Magiati et al, 2017). Three of the assessment studies used EMA to assess everyday state anxiety (i.e.…”
Section: Summary and Critique Of Evidence: Assessment Studiesmentioning
confidence: 99%
“…Methodologically, it is also important to note here that pure resting-state studies more often reported that participants were given some time to adapt to the laboratory context before autonomic measurement began. This might have influenced the findings as autistic participants are known to struggle with new environments (Lau et al, 2019). Similarly, studies that reportedly focused on solely resting-state measurement, as compared to those in which the resting-state measurement was followed by a task (cognitive or physical), were more likely to report group differences.…”
Section: Discussionmentioning
confidence: 99%
“…Research directions for group-based social interactions within a virtual environment also remain largely unexplored. Evidence suggests that individuals with social challenges most frequently avoid loud, crowded spaces and may benefit from a modifiable, virtual environment to improve social skills (Lau et al, 2020). To further enhance sensory immersion, it may be beneficial from an engagement standpoint to incorporate non-player characters and auditory features such as environmental ambient sound into the virtual world, thereby simulating real-life experiences of small and large group gatherings.…”
Section: Limitationsmentioning
confidence: 99%